The recording of Aboriginal and Torres Strait Islander status in general practice clinical records: a cross‐sectional study. (29th June 2015) - Thomson, Allison; Morgan, Simon; O'Mara, Peter; Tapley, Amanda; Henderson, Kim; van Driel, Mieke; Oldmeadow, Christopher; Ball, Jean; Scott, John; Spike, Neil; McArthur, Lawrie; Magin, Parker
Abstract: Objectives: To document the frequency of recording of Aboriginal and Torres Strait Islander status in general practice (GP) clinical records and to establish associations of this recording. Methods: Cross‐sectional analysis of recording of patients' Aboriginal and Torres Strait Islander status in GP clinical records from GP training practices in four Australian states. Results: Of the 9, 704 clinical records examined, the patients' Aboriginal and Torres Strait Islander status had been documented in 5, 165 (53.2%). Higher rates of recording were associated with older patient age, practices outside a major city, patients who were not new to the practice and the patient being Aboriginal and Torres Strait Islander. In encounters with Aboriginal and Torres Strait Islander patients, the patient's status had been documented in 82% of records. Those attending larger practices were less likely to have had their status recorded. Conclusions: This is the first report of Aboriginal and Torres Strait Islander status recording in GP clinical records. Almost 20% of Aboriginal and Torres Strait Islander patients did not have their status recorded in the clinical record, with indications that recording may be unsystematic. Implications: Our findings reinforce the need for a systematic approach to identification of Aboriginal and Torres Strait Islander status in general practice and will inform policy and practice in this important area.